Preparation of a Sn@SnO2@C@MoS2 composite as a high-performance anode material for lithium-ion batteries. Issue 19 (22nd April 2016) - Huang, Youguo; Pan, Qichang; Wang, Hongqiang; Ji, Cheng; Wu, Xianming; He, Zeqiang; Li, Qingyu
Abstract : Sn@SnO2 @C nanosheets decorated with MoS2 are prepared via a facile ball milling and hydrothermal method, and the Sn@SnO2 @C@MoS2 composite shows high capacity and long-term cycling stability when used as an anode material for lithium-ion batteries. Abstract : A new type of Sn@SnO2 @C@MoS2 composite, composed of Sn@SnO2 @C nanosheets and decorated with MoS2, exhibits significantly improved electrochemical performance. This composite has excellent long-term cycling stability (841 mA h g −1 at 1.0 A g −1 after 400 cycles) and superior high-rate capability (458.3 mA h g −1 at 10.0 A g −1 ) due to the strong synergistic effect between the MoS2 and Sn@C nanosheets.